Disassembling peptide-based fibres by switching the hydrophobic-hydrophilic balance - Meijer, Joris T; Henckens, Marloes J A G; Minten, Inge J; Löwik, Dennis W P M; van Hest, Jan C M (Soft matter, 2007)
Amyloid-like model peptides, modified on the N-terminus with an alkyl tail and on the C-terminus with a PEG chain, yielded fibres that were susceptible to triggered disassembly by removal of the alkyl chain, which affected the hydrophobic-hydrophilic balance.Amyloid-like model peptides, modified on the N-terminus with an alkyl tail and on the C-terminus with a PEG chain, yielded fibres that were susceptible to triggered disassembly by removal of the alkyl chain, which affected the hydrophobic-hydrophilic balance.